Real work experiences, practices and adverse events associated with long term usage of N95 respirators during the COVID-19 pandemic – A cross-sectional survey amongst Indian physicians - Henry, Renoy; Krishnamoorthy, Smitha; Ravikumar, Anjali; Pradeep, Manu; Padmanabhan, Dakshin Sitaram; Menon, Raviraj; Surendran, Sandeep (International Journal of Occupational Safety and Health, 2022)
Introduction: Doctors are at increased risk of exposure to SARS-CoV-2 virus, and use of N95 respirators has emerged as a key preventive measure. This study aimed to study the real-world experiences, practices and adverse effects of N95 respirator usage amongst doctors of India. Methods: An analytical, cross-sectional online survey was conducted between November 2020 and January 2021. Real-world usage characteristics of N-95 respirators were collected via a pre-validated questionnaire (use, reuse, wearing and disposal practices) and compared amongst different sub-cohorts. Results: 453 responses from physicians were analyzed. The most important adjunct to the N95 respirator perceived by the respondents was the full-face shield (81.9%). Most doctors had to purchase extra mask per month (median = 5) and this was more amongst the medical specialties (p = 0.006). Highest mean VAS scores for adverse events were reported for breathing on exertion (6.62 ± 2.25) and ear pain (6.34 ± 2.69). VAS ear pain was higher in ages < 40 and doctors working in the public sector (p = 0.017 and p = 0.019 respectively). Conclusion: There are many inadequacies with regard to proper mask removal and doffing techniques among doctors in India. The major adverse effects faced by the doctors on prolonged mask usage were ear pain and breathing on exertion. However, it can be noted in spite of these deficiencies; there is generally good adherence to protocols and good practices of mask usage in hospital setting.